2001
DOI: 10.1053/jhep.2001.24268
|View full text |Cite
|
Sign up to set email alerts
|

Sen Virus Infection and Its Relationship to Transfusion–Associated Hepatitis

Abstract: SEN virus (SEN-VAfter cloning of the hepatitis C virus (HCV) 1 and development of sensitive serologic and molecular assays for this pathogen, a dramatic decline in the incidence of transfusionassociated hepatitis occurred. 2,3 However, approximately 10% of transfusion-associated hepatitis cases 4 and 20% of community-acquired hepatitis cases 5 do not have a defined etiology suggesting the existence of additional causative agents. Hepatitis G virus (HGV), 6 also known as GB virus C (GBV-C), 7 was initially sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
184
6
5

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(207 citation statements)
references
References 24 publications
12
184
6
5
Order By: Relevance
“…While the immune system appears to play a role in controlling virus replication [26,27], the mechanisms by which TTV establishes persistent infection remain unclear. While pre-or peri-natal infection may induce partial immunotolerance, that would not explain how infection with antigenically distinct genotypes of TTV can occur later in life [20,22].…”
Section: Unique Aspects Of Ttvmentioning
confidence: 99%
See 1 more Smart Citation
“…While the immune system appears to play a role in controlling virus replication [26,27], the mechanisms by which TTV establishes persistent infection remain unclear. While pre-or peri-natal infection may induce partial immunotolerance, that would not explain how infection with antigenically distinct genotypes of TTV can occur later in life [20,22].…”
Section: Unique Aspects Of Ttvmentioning
confidence: 99%
“…For example, following the suggestion from the original discoverers of TTV [20], it has been proposed that infection with the prototype genotype 1 strain of TTV may be associated with post-transfusion hepatitis [21]. More recently, infection with the TTV genotypes described as SENV-D and SENV-H was found to be much more prevalent in patients with post-transfusion non-A-E hepatitis than transfused patients without hepatitis (92% compared with 24%) [22]. However, as is typical in TTV research, further work has tended to discount such an association [23,24].…”
Section: Disease Associations Of Ttvmentioning
confidence: 99%
“…In preliminary studies, SEN V was reported to be associated with the same transmission risk factors as HCV and HBV; transfusion of blood products and abuse of parenteral illicit drugs. 19,20 Moreover, there was a suggestion of an association with NANE hepatitis. 19 We decided to perform a cross-sectional analysis (i.e., at specific time points) on an unselected sample of our liver transplant recipients for the presence of SEN V. We believed that our patients, who received not only a liver allograft but many blood products in the course of their pretransplantation and posttransplantation care, would be at risk for the transmission of unknown blood-borne viruses.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Moreover, there was a suggestion of an association with NANE hepatitis. 19 We decided to perform a cross-sectional analysis (i.e., at specific time points) on an unselected sample of our liver transplant recipients for the presence of SEN V. We believed that our patients, who received not only a liver allograft but many blood products in the course of their pretransplantation and posttransplantation care, would be at risk for the transmission of unknown blood-borne viruses. Moreover, because these patients are immunosuppressed, they would be the most likely group to develop persistent transaminitis of untreated hepatotrophic viral infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation